Regulation of CCL5 Expression in Smooth Muscle Cells Following Arterial Injury - Liu, Huan; Ning, Huan; Men, Hongchao; Hou, Rong; Fu, Mingui; Zhang, Hailin; Liu, Jianguo (PLOS ONE, 2012)
Chemokines play a crucial role in inflammation and in the pathophysiology of atherosclerosis by recruiting inflammatory immune cells to the endothelium. Chemokine CCL5 has been shown to be involved in atherosclerosis progression. However, little is known about how CCL5 is regulated in vascular smooth muscle cells. In this study we report that CCL5 mRNA expression was induced and peaked in aorta at day 7 and then declined after balloon artery injury, whereas IP-10 and MCP-1 mRNA expression were induced and peaked at day 3 and then rapidly declined. The expression of CCL5 receptors (CCR1, 3 & 5) were also rapidly induced and then declined except CCR5 which expression was still relatively high at day 14 after balloon injury. In rat smooth muscle cells (SMCs), similar as in aorta CCL5 mRNA expression was induced and kept increasing after LPS plus IFN-gamma stimulation, whereas IP-10 mRNA expression was rapidly induced and then declined. Our data further indicate that induction of CCL5 expression in SMCs was mediated by IRF-1 via binding to the IRF-1 response element in CCL5 promoter. Moreover, p38 MAPK was involved in suppression of CCL5 and IP-10 expression in SMCs through common upstream molecule MKK3. The downstream molecule MK2 was required for p38-mediated CCL5 but not IP-10 inhibition. Our findings indicate that CCL5 induction in aorta and SMCs is mediated by IRF-1 while activation of p38 MAPK signaling inhibits CCL5 and IP-10 expression. Methods targeting MK2 expression could be used to selectively regulate CCL5 but not IP-10 expression in SMCs.